m^2+10m+9=0

Simple and best practice solution for m^2+10m+9=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m^2+10m+9=0 equation:


Simplifying
m2 + 10m + 9 = 0

Reorder the terms:
9 + 10m + m2 = 0

Solving
9 + 10m + m2 = 0

Solving for variable 'm'.

Factor a trinomial.
(9 + m)(1 + m) = 0

Subproblem 1

Set the factor '(9 + m)' equal to zero and attempt to solve: Simplifying 9 + m = 0 Solving 9 + m = 0 Move all terms containing m to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + m = 0 + -9 Combine like terms: 9 + -9 = 0 0 + m = 0 + -9 m = 0 + -9 Combine like terms: 0 + -9 = -9 m = -9 Simplifying m = -9

Subproblem 2

Set the factor '(1 + m)' equal to zero and attempt to solve: Simplifying 1 + m = 0 Solving 1 + m = 0 Move all terms containing m to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + m = 0 + -1 Combine like terms: 1 + -1 = 0 0 + m = 0 + -1 m = 0 + -1 Combine like terms: 0 + -1 = -1 m = -1 Simplifying m = -1

Solution

m = {-9, -1}

You can always share this solution

See similar equations:

| m^2+5m+6=0 | | 5x^2+10x+5=180 | | 6(1+8x^3)=9 | | x^3+6x^2=4x+24 | | 5x^2-7x+2=0 | | 2x^2-11x+15=0 | | 4x^2=12x | | 8x^2=72x | | 2x^2-2=-5x-1 | | 0=3x^2-5x-9 | | 3x^2-6x+9=0 | | 3q^2+16=-19q | | (-2x^2+3y^3)+(6x-5)=0 | | 2x^2+6x+4=0 | | 2x^2-5x-75=0 | | 2x^2-10x+18=0 | | 9s^2+3s-20=x | | (x-1)(x^2-4)+2(x-1)(x+2)=(x-1)P | | 9x^2-4.5x-3.5=0 | | 6x^2-5x-14=0 | | x^4-7x-18=0 | | x^2-8x+18=0 | | x^2-8b+18=0 | | 30a^2+am-m^2=0 | | 30a^2+am-m^2=o | | 12s^2+11st-5t^2=0 | | 14x^2+11yx-15y^2=0 | | 3x^2+8=0 | | -2v^2-v+12=-3v^2+6v | | x^2+15x-64=0 | | 2x^2+8x-2=0 | | 12x^2-x-20=0 |

Equations solver categories